(untitled) (KYAMC Journal, 2019)
Background: In Bangladesh, violence plays a detrimental role in our daily lives directly or indirectly. The country experiences high levels of violence, with incidents of violence being reported in mass media daily. Objective: The objectives of this study were to assess the demographic and social factors associated with assault incidents as well as to establish the type of injuries suffered by the victims of assault. Materials and methods: This study was a retrospective, cross-sectional survey, undertaken at the casualty department of the Sherpur Upazilla Health Complex, Bogura, Bangladesh from 12th November 2016 to 11th December 2016. All patients who attended for injuries due to alleged assault (interpersonal violence) and met the inclusion criteria were included in the study. A total of 72 patients were assaulted which are selected as subjects of the study out of 131 casualties. Results: The majority of the victims were males (51.38%), 27.76% were single and 90.27% were of Muslims. The age group of the majority (31.94%) ranged between 21 and 30 years. Most the respondents (68.05%) had injuries to more than one part of the body. Among the assaulted patients, 65.27% had more than one type of injury. The majority of the victims of assault (58.33%2) were admitted for in-hospital treatment. Conclusion: The study revealed that majority of typical victims of assault treated at Health Complex was males between the ages of 21 and 30 years suffering from minor injuries, mainly to the abdomen and chest. KYAMC Journal Vol. 10, No.-1, April 2019, Page 13-16